Healthcare-seeking behavior and out-of-pocket payments in Erbil, Kurdistan Region of Iraq - Nazar P. Shabila; Kochr A. Mahmood; Karwan M. M-Amin; Kazhan I. Mahmood; Abubakir M. Saleh (BMC, 2024)
Abstract Background Understanding healthcare-seeking behavior and examining health expenditures can help determine possible barriers to accessing healthcare and direct more effective and inclusive healthcare systems. This study aimed to evaluate healthcare-seeking behavior and out-of-pocket healthcare expenditure in a sample of the population in Erbil, Iraq. Methods We conducted this cross-sectional study in Erbil, Kurdistan Region of Iraq, from October to December 2023. A convenience sample of 414 adults completed a self-administered online survey. The following data were collected: recent illness, sociodemographic characteristics, type of healthcare received, and cost of healthcare. Results The most common health conditions reported were communicable diseases (16.3%), musculoskeletal problems (13.1%), and noncommunicable diseases (12.7%). Approximately 85% of patients with health conditions requiring care sought healthcare; most visited private clinics (46.3%) and private hospitals (18.6%). The median total out-of-pocket healthcare expenditure in US dollars was 117.3 (interquartile range (IQR) = 45.6-410.0). The median total cost was much greater for participants who first visited a private health facility (USD 135.5, IQR = 57.3-405.6) than those who first visited a public facility (USD 76.8, IQR = 16.1-459.7). Participants ≥ 60 years spent significantly more than those < 14 years (USD 332, 95% CI = 211-453, p < 0.001). Evermarried participants spent significantly more than unmarried (USD 97, 95% CI = 1 to 192, p = 0.047). Health expenditures were significantly greater for noncommunicable diseases than infectious diseases (USD 232, 95% CI = 96-368, p = 0.001). After adjusting for covariates, age ≥ 60 years was independently associated with higher spending (USD 305, 95% CI = 153-457, p < 0.001). Conclusions Most participants sought care from formal health services, preferring the private sector. Seeking care from private facilities incurred significantly higher costs than seeking care from public ones, which suggests potential barriers to accessing healthcare, particularly affordability. The findings underscore the importance of evaluating existing healthcare policies to enhance effectiveness and identify areas for improvement. This study can help policymakers and healthcare providers design effective interventions, allocate resources efficiently, and improve healthcare delivery.